Novel coalescence-driven grain-growth mechanism during annealing/spark plasma sintering of NiO nanocrystals. Issue 15 (December 2017) - Akkiraju, K.; Kashyap, S.; Srivastav, Ajeet K.; Chawake, Niraj; Bichler, L.; Murty, B.S.
Abstract: A novel oriented attachment growth mechanism of nanograins has been suggested for spark plasma sintering and annealing of NiO nanopowder. A hierarchical microstructure built by cube-shaped nanograins was observed during pressure-less spark plasma sintering at temperatures above 1000 °C and when the powders were annealed in ambient atmosphere at and above 700 °C. Irrespective of the processing method used, a rotation assisted grain attachment of irregularly shaped nanocrystals results in such a microstructure with parallel epitaxy, twinning or line defects at the grain interface. The unique microstructural features and the governing factors for the attachment process have been discussed.